THE PECULIARITIES OF THE TRANSLATION OF REALIA IN ENGLISH AND UZBEK - Turakulova Lola Khamidjanovna (Western European Studies, 2023)
Realia refers to the objects, customs, and cultural aspects specific to a particular language or region. Translating realia poses unique challenges, particularly when dealing with the English and Uzbek languages. This article explores the difficulties and peculiarities encountered in the translation of realia between these languages, and highlights the importance of considering various factors in order to achieve accurate and culturally appropriate translations.
Keywords: Realia; semantic analyses; languages; culturals